Proyecto de factibilidad para la implementación de una empresa productora y comercializadora de té de guayusa en el cantón Lago Agrio, provincia de Sucumbíos, para el año 2015 - Jiménez Girón, Lilia Magali (2015)
The use of infusions in the country has increasingly accepted by the variety and quality of them. Health, fair trade and attractive prices are important to the consumer aspects. This thesis is focused on making a "Feasibility Project for the Implementation of a producer and marketer of tea guayusa in the canton Lago Agrio, Sucumbios province"; in order to meet the needs and expectations demanded by consumers with a natural product developed from the leaves of a plant native to the Amazon, as is the guayusa. For the implementation of the project and fulfillment of the objectives set methods and techniques, which allowed to obtain the information necessary for its development within technical survey was used, with a sample of 381 surveys for the plaintiffs were used, and 10 surveys for bidder’s tea herbs between commissaries and supermarkets. The development of this project was also based on the following six studies: Market research, technical, administrative, economic, financial and environmental assessment, same as detailed below. For the market research the economically active population of Lago Agrio Canton is 37,575 inhabitants was used, according to the population census of 2010, a figure that is projected for five years, after tabulating surveys different demands was determined as effective we have 297.486 boxes of tea guayusa 25 units in the first year, with users who buy the product to the new company, as we have 285.846 annual unmet demand guayusa tea boxes of 25 units. In the case of supply there are no companies that produce and market guayusa tea in the Lago Agrio Canton, data for the study were obtained from market similar products such as tea herbs. As for the technical study the company will have an installed capacity of 202,752 boxes of tea guayusa and work with a capacity of 95% in the first year from the second year by 100% to end the life of the project capacity, location the company determined by the Macro Trace and microlocalization, therefore, be located on Calle La Pinta and San Cristobal parish Nueva Loja, Lago Agrio canton, Province of Sucumbios, because it has all the requirements necessary for its operation. As for the administrative and legal study, the corporate name of the company will be Aromatics Lago Agrio, its constitution limited company, organization charts and manual functions for each of the workers developed the development of activities. The financial study discloses the total investment of the project is $ 114.108,40 US dollars of America, will have 74% equity and 26% debt capital, financed by the National Development Bank, with an interest rate of 11.20% per annum. Within the financial evaluation it found that the project is feasible according to economic indicators such as: the net present value USD $ 8.086,99 US dollars of America, the internal rate of return 14%, cost benefit ratio, for every dollar invested will get a profit of $ 0.29 cents of United States of America, payback period of capital, 3 years, 5 months, 22 days, and the sensitivity analysis with increased costs of 7.46% and decrease in revenues of 4.40% as a result gives us 0.99, which is less than 1, therefore, the project is not sensitive to changes generated. In the environmental study, appropriate measures will be taken into consideration to prevent damage to our environment, social environment where boost socio-economic development of the canton through the generation of jobs was also analyzed.